Catalytic Synthesis of Benzene Directly From Methane - 王林胜 陶龙骧 谢茂松 徐桂芬 王学林 徐奕德 黄家生 (中国科学通报：英文版, 1994)
Methane is a major component of natural gas. The activation and selectiveconversion of methane are one of the most difficult problems in chemistry because itis a thermodynamically most stable compound with an inert gas-like configuration.The oxidizing conditions usually are favourable for the conversion of methane;however, it is difficult to control and minimize the complete oxidation of methane to